2015
DOI: 10.1007/s10554-015-0720-0
|View full text |Cite
|
Sign up to set email alerts
|

Systolic and diastolic myocardial mechanics in hypertrophic cardiomyopathy and their link to the extent of hypertrophy, replacement fibrosis and interstitial fibrosis

Abstract: Aim of the present study was to investigate the relations between myocardial mechanics and the extent of hypertrophy and fibrosis in hypertrophic cardiomyopathy (HCM). Forty-five consecutive patients with HCM and 15 subjects without structural heart disease were included. Cardiac magnetic resonance with late gadolinium enhancement (LGE) imaging was performed to evaluate biventricular function, LV mass index and presence/extent of LGE, expression of replacement fibrosis. Myocardial T1 relaxation, a surrogate of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(19 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…Our results show that sarcomeric mutations, which disrupt the regulation of the thin filament (decreased perm 50 , decreased k offH , increased k on ) in a way that has a downstream effect of increasing Ca 2+ sensitivity, increase the degree of repolarization reserve reduction necessary for EADs to emerge and decreases the frequency of EAD occurrence. Combined with the observations from the previous studies, this suggests that the enhanced arrhythmogenicity seen in HCM is not due to altered Ca 2+ sensitivity, but rather due to HCM-induced ionic remodeling as suggested by Coppini et al (Coppini et al, 2013) or from secondary effects of myofilament remodeling at the tissue level, such as hypertrophy and fibrosis (Chan et al, 2014; Nucifora et al, 2015). …”
Section: Discussionsupporting
confidence: 66%
“…Our results show that sarcomeric mutations, which disrupt the regulation of the thin filament (decreased perm 50 , decreased k offH , increased k on ) in a way that has a downstream effect of increasing Ca 2+ sensitivity, increase the degree of repolarization reserve reduction necessary for EADs to emerge and decreases the frequency of EAD occurrence. Combined with the observations from the previous studies, this suggests that the enhanced arrhythmogenicity seen in HCM is not due to altered Ca 2+ sensitivity, but rather due to HCM-induced ionic remodeling as suggested by Coppini et al (Coppini et al, 2013) or from secondary effects of myofilament remodeling at the tissue level, such as hypertrophy and fibrosis (Chan et al, 2014; Nucifora et al, 2015). …”
Section: Discussionsupporting
confidence: 66%
“…The analysis of myocardial strain offers new insight into disease’s mechanisms: intramural functional abnormalities have been shown to extend beyond the presence of late gadolinium enhancement (LGE) in patients with hypertrophic cardiomyopathy (HCM), as intramural systolic strain is abnormal in hypertrophied segments as compared to segments without hypertrophy, irrespective of the presence of LGE [60]. However, a linear correlation between myocardial strain and the amount of LGE has been shown in different studies [15, 61, 62], both at the global and segmental levels, so that it has been inferred that strain analysis might be considered in the future to indirectly detect the presence of scar, without need of contrast agent [62]. …”
Section: Clinical Applicationmentioning
confidence: 99%
“…The severity of LVOT obstruction is an important pathognomonic factor in disease progression and clinical outcome 1,2 . Histological and imaging studies have identified replacement and interstitial fibrosis as the pathological basis for systolic and diastolic dysfunction, respectively 15,16 . The extent of hypertrophy is inversely associated with regional systolic function and correlates positively with myocardial scarring, even in asymptomatic patients 17,18 .…”
Section: Discussionmentioning
confidence: 99%